How Ready Are Gym Users to Refrain from Performance-Enhancing Substances? The Transtheoretical Model of Change as a Theoretical Framework - Ahmed Abbas Darjal, Arkan Bahlol Naji, (Pakistan Journal of Medical & Health Sciences, 2022)
Methods: A descriptive predictive correlational design was be used to guide this study.The study included a convenience sample of male gym users who agreed to participate in this study. The study subjects were recruited from six private gyms.The study instrument includes subjects’ sociodemographic characteristics of age, living arrangement, family’s socioeconomic status, the performance-enhancing substances that the gym users use. It also includes the Transtheoretical Model of Change measures of Stages of Change for Performance-Enhancing Substances Scale (Short Form), the Stages of Change for Performance-Enhancing Substances Scale (Continuous Measure), the Processes of Change for Performance-Enhancing Substances Scale, the Self-Efficacy for Performance-Enhancing Substances Scale, the Decisional Balance Scale for Performance-Enhancing Substances. Data were analyzed using the statistical package for social science (SPSS) for windows, version 28. Results: The study results revealed that around a half are in the Precontemplation Stage of Change, followed by those who are in the Contemplation Stage of Change, those who are in the Action Stage of Change, those who are in the Termination Stage of Change, and those who are in the Preparation Stage of Change. Conclusion: The greater the Pros, the higher the Stages of Change for performance-enhancing substance use the gym user would therein.The greater the Social Liberation, the higher the Stages of Change for performance-enhancing substance use the gym user would therein. The greater the Helping Relationships, the higher the Stages of Change for performance-enhancing substance use the gym user would therein. Keywords: Gym Users; Performance-Enhancing Substances; Transtheoretical Model